Pacific Biological Laboratory
Pacific Biological Laboratory, 800 Cannery Row, Monterey Ca. Bruce Ariss, editor and mural painter, and Doctor Susan Shillinglaw with tourers milling at the back of the Laboratory. This was on the same day as the tour of the Steinbeck home and the Herbert Ranch. Negative and digital copy only. No hard copy.